Dinamika Loyalitas Konsumen Gen Z: Peran Strategis Brand Ambassador Dan Kualitas Produk dalam Ekosistem Pemasaran Kecantikan Wardah - Lestari, Putri Ayu; Paramita S, Novia; Gunawan, Didik; Puspaningrum, Cici (Cattleya Darmaya Fortuna, 2025)
The rapid growth of Indonesia's beauty industry has made consumer loyalty a strategic focus for cosmetic brands, particularly among Generation Z. This study analyzes the influence of brand ambassadors and product quality on customer loyalty in the context of Wardah, a leading halal beauty brand. Using a quantitative method, a survey was distributed to 100 respondents who follow Ayana Jihye Moon—Wardah's brand ambassador—on Instagram. Data analysis employed multiple linear regression, t-tests, F-tests, and classical assumption tests (validity, reliability, normality, multicollinearity, and heteroscedasticity). Results indicate that the brand ambassador has a significant positive effect on customer loyalty (t = 2.706, p < 0.05), while product quality does not show a significant effect (t = 1.003, p > 0.05). However, both variables simultaneously influence customer loyalty significantly (F = 43.756, p < 0.05). These findings highlight that the emotional connection built through a well-chosen brand ambassador, especially one aligned with consumer values like Ayana, plays a more decisive role in forming brand loyalty among Gen Z than product quality alone. While product quality remains essential, it is insufficient without effective communication and brand representation. This research contributes to understanding consumer behavior in the digital era and offers insights for marketers to tailor strategies for maintaining brand loyalty in a competitive market.